Natural incidence of parasitoids in eggs of Pentatomidae found in soybean in Planaltina, DF, Brazil - De Medeiros, Maria Alice (1998)
Fil: De Medeiros, Maria Alice. Centro Nacional de Pesquisa de Hortaliças (CNPH). Brasília, DF.